PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN RUMUS SEGITIGA JKW MATERI JARAK KECEPATAN DAN WAKTU DI SD NEGERI 39 TANJUNG RIA - Sri Astutik; Indri Astuti; Dodi Sukmayadi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
Mathematics lessons in elementary schools are synonymous with difficult subjects, especially in distance, speed and time. This is evidenced by the results of the pre-research questionnaire which stated that 63% of students did not like mathematics. Therefore we need an interesting learning media, one of which is learning videos. This study aims to determine the feasibility and student response to the development of learning videos using the JKW triangle formula for distance, speed and time. The research was carried out in a research and development manner using the ADDIE research model with research and development stages namely analyze, design, development, implementation, and evaluation. The data collection tools used were expert validation sheets and student response questionnaires. Based on the results at the validation stage, the eligibility level in terms of media was 92%, in terms of material it was 92.9% and in terms of design it was 92.4% with an average feasibility percentage of 92.4%. Then after revisions were made in accordance with the validator's suggestions for improvement, product trials were carried out in stages, namely one-to-one trials with three (3) students, small group trials of six (6) students and large group trials of 29 grade V SD students. Country 39 Tanjung Ria. Through the implementation stage, students' responses to product development produced positive responses, as evidenced by the results of the questionnaire which obtained a percentage of 74% cognitive, 81% on the affective aspect and 72% on the conative aspect. At the implementation stage, students gave a positive response 93.1% on the benefits aspect, 92.2% on the relevance aspect and 92.1% on the contextuality aspect. Based on the results of this research, the product development in the form of learning videos on distance, speed and time materials is a video that is valid and feasible by experts and gets a positive response from students.